Corporate governance in South Asia trends and challenges. - Kirchmaier, Tom (Asian Development Bank, 2020)
The four core areas analyzed are (i) corporate governance legal frameworks, (ii) board structure and board diversity, (iii) corporate governance of state owned enterprises, and (iv) anti money laundering and compliance. The findings are relevant for developing countries around the world, as corporate governance impacts evolving challenges such as the coronavirus disease pandemic, climate change, and sustainable global trade.